(untitled) (Research, Society and Development, 2022)
Objective: To analyze the association between endometriosis and the occurrence of placenta previa. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “endometriosis”, “endometrioma”, “chocolate cyst”, “placenta previa”, “low lying placenta” and “abnormal placenta”. Full articles, available in Portuguese, English or Spanish, were included; published between January 2016 and December 2021; who performed a comparative study between an experimental group and a control group; studies that showed the incidences of placenta previa with statistical data. Results: 11 articles made up the final sample of this study, with a higher frequency of publication in 2019 (n: 03). Most of the studies used the retrospective cohort study, with a moderate level of evidence (III). All studies compared pregnant women with or without endometriosis, all of which showed that women with endometriosis had a higher rate of placenta previa, with Odds Ratio ranging from 0.56 to 6.42 and statistically significant. Conclusion: The findings of this research suggest that, although based on a small number of studies, endometriosis may be a possible risk factor for the occurrence of placenta previa, excluding confounding factors, which were not considered for analysis. These findings can help health professionals to be more attentive to possible complications during the course of pregnancy and delivery.